Brain-derived neurotrophic factor and epilepsy: a systematic review. (December 2018) - Iughetti, Lorenzo; Lucaccioni, Laura; Fugetto, Francesco; Predieri, Barbara; Berardi, Alberto; Ferrari, Fabrizio
Abstract: Several in vitro, ex vivo and in vivo studies imply brain-derived neurotrophic factor (BDNF) in the pathophysiology of epilepsy. Aim of our work is to report the most important findings regarding BDNF and its potential role in epilepsy. We targeted those publications addressing both in vitro and in vivo evidences of relationship between BDNF and epilepsy. Basic researches, randomized trials, cohort studies, and reviews were contemplated to give a breadth of clinical data. Medline, CENTRAL, and Science Direct were searched till August 2017 using keywords agreed by the authors. Together with a defined role in developmental and mature brain, BDNF has excitatory effects in neuronal cultures and animal brain slices. Furthermore, both BDNF and its conjugated receptor (i.e. Tropomyosin receptor kinase B or TrkB) are increased in animal models and humans with epilepsy, particularly in the temporal and hippocampal areas. Acute injection of BDNF in brain of mice induces seizures, which are almost or totally abolished blocking its transcription and pathway. Chronic infusion of BDNF is conversely associated with a decreased neuronal excitability, probably via several mechanism including an increase in central levels of neuropeptide Y (NPY), altered conductance of chloride, and downregulation of TrkB. While genetic studies are inconclusive, serum BDNF is more frequently higher in patients with epilepsy and appears to be correlated to severity of disease. Current evidences suggest that inhibiting BDNF-TrkB signaling and reinforcing the NPY system could represent a potential therapeutic strategy for epilepsy, especially for temporal lobe epilepsy. Highlights: BDNF as neurotrophic factor is important in development and maintenance of neuronal populations in the central nervous system. BDNF is expressed by neurons but is also found in astrocytes and microglia. High BDNF expression is found in the hippocampus. BDNF potentiates synaptic transmission influencing both structure and function of inhibitory cells, namely GABA-ergic neurons. BDNF reduction in specific brain areas is are associated with neurodegenerative and neuropsychiatric diseases, and obesity Inhibiting BDNF pathway could represent a potential therapeutic strategy for epilepsy.